The first occurrence of Kemp’s Ridley turtle (Lepidochelys kempii) in Raja Ampat, Indonesia - FERLIANA WIDAYSARI; AJI NUGROHO; GULAM ARAFAT; RAHMADI SUNOKO; RUDI ALEX WAHYUDIN; MOHAMMAD SAYUTI; ELISA BAKKULA; FERDIEL BALLAMU (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Widaysari F, Nugroho A, Arafat G, Sunoko R, Wahyudin RA, Sayuti M, Bakkula E, Ballamu F. 2023. The first occurrence of Kemp’s Ridley turtle (Lepidochelys kempii) in Raja Ampat, Indonesia. Biodiversitas 24: 4934-4942. Territory Indonesian waters are one of the waters in Southeast Asia that have been a turtle habitat; six of the seven types of turtles live in these waters, and Kemp ridley's turtle (Lepidochelys kempii) is the seventh reported to have recently emerged. The research objectives of the study were to identify the area location emergence of Kemp’s Ridley turtle, determine morphology, and release Kemp’s Ridley turtle. Location identification was based on the Raja Ampat District Central Statistics Agency data. Visual identification of turtles proceeds by looking at their morphology, namely carapace shape, number of vertebral and costal scutes, the form of the plastron, number of inframarginal scutes, and appearance of head shape juxtaposed on External Morphology. The water area where Kemp’s Ridley turtle was found had a constant temperature, moderate wind speed, high humidity, and rainfall. The results of identifying the turtle morphology matched Kemp’s Ridley turtle. After outreach to the community, Kemp’s Ridley turtles were released into nature. The first appearance of the Kemp’s Ridley turtle in Indonesia is undoubtedly an exciting study material for further study regarding the migration map, distribution, and other factors that cause changes in its migration.